PSORI-CM02 Formula Increases CD4+ Foxp3+ Regulatory T Cell Frequency and Ameliorates Imiquimod-Induced Psoriasis in Mice - Chen, Haiming; Liu, Huazhen; Lu, Chuanjian; Wang, Maojie; Li, Xiong; Zhao, Hui; Yan, Yuhong; Yu, Wanling; Han, Ling; Dai, Zhenhua (Frontiers in Immunology, 2018)
Psoriasis is an autoimmune and inflammatory disease, which is estimated to affect 2–3% of the population in the world. PSORI-CM02 is an empirical formula of Chinese medicine optimized from Yin Xie Ling, which is widely used to treat psoriasis in China for decades. However, its antipsoriatic mechanisms are still not well understood. Here, we explored the therapeutic effects of PSORI-CM02 on psoriasis and its mechanisms of action in imiquimod-induced psoriasis-like mouse models and human HaCaT cells. In experiments in vitro, PSORI-CM02 significantly inhibited HaCaT cell proliferation in dose-dependent and time-dependent manners. Furthermore, it hindered the progression of HaCaT cell cycle and arrested HaCaT cells at G1 phase. On the other hand, our in vivo studies demonstrated that PSORI-CM02 dramatically reduced psoriasis area and severity index scores and lesion temperature in imiquimod-induced psoriatic mice. The antioxidative activities of glutathione, catalase, and superoxide dismutase were increased while oxidative activity of malonaldehyde was markedly decreased after treatments with PSORI-CM02. PSORI-CM02 also suppressed the mRNA expression of proinflammatory cytokines, including TNF-α, IL-6, and IL-17, and lowered their protein levels in the serum as well. In addition, PSORI-CM02 could reduce the expression of IKKα and NF-κB in psoriatic skin tissue. It also upregulated the proportion of CD4+ Foxp3+ regulatory T cells (Tregs) in both lymph nodes and spleens and promoted CD4+ CD25+ Treg proliferation in vitro. Taken together, our research demonstrated that PSORI-CM02 inhibited HaCaT cell proliferation by arresting them at G1 phase and alleviated systemic inflammation and psoriasis in mice via altering the oxidative/anti-oxidative status, tipping the balance between Th17 responsiveness and CD4+ Foxp3+ Treg generation, and suppressing the expression of proinflammatory cytokines as well as NF-κB signaling.